Filmowe rejestracje teatru - opis i problematyzacje zjawiska - DOMALEWSKI, ADAM (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
The paper attempts to distinguish film recordings of theater from the TV theater genre. The decisive criterion for this distinction proposed by the author is the chronology of the production process - film recordings of theater performances provide a record of pre-existing theater performances, whereas TV theatre includes all theatre-like productions created for the small screen and which do not have their own stage ‘odginali In each of these cases there are different tasks and difficulties facing producers and executors. The next part of the article focuses on film recordings of theater: the reasons for which they are made (documentation, dissemination, promotion) and the differences between their types. Referring to the work of Jacek Wachowski, the author also presents a brief discussion about the possibilities and consequences of technical mediation of any performances, not only theatrical shows. The article concludes with an attempt to define the status of the film recording of a performance in relation to its original theatrical nature (the “residuum of the theater”).